2015
DOI: 10.1017/s0950268815001442
|View full text |Cite
|
Sign up to set email alerts
|

Human anthrax outbreak associated with livestock exposure: Georgia, 2012

Abstract: Human anthrax cases reported in the country of Georgia increased 75% from 2011 (n = 81) to 2012 (n = 142). This increase prompted a case-control investigation using 67 culture- or PCR-confirmed cases and 134 controls matched by residence and gender to investigate risk factor(s) for infection during the month before case onset. Independent predictors most strongly associated with disease in the multivariable modelling were slaughtering animals [odds ratio (OR) 7·3, 95% confidence interval (CI) 2·9-18·1, P 1 km;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
(33 reference statements)
0
20
1
Order By: Relevance
“…We found that males had a higher incidence than females, in particular for adults, probably due to the occupational exposure. Among herders and farmers, men are usually more exposed to livestock than women by undertaking most agricultural activities such as pasturing and slaughtering [ 13 , 14 ]. Although incidences of human cases and livestock cases were significantly correlated, inconsistency was found in their spatial distributions in some provinces, e.g., Tibet and Sichuan, likely due to underreporting of anthrax case in livestock or the possibility that more than one person may contract the disease from a single animal [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that males had a higher incidence than females, in particular for adults, probably due to the occupational exposure. Among herders and farmers, men are usually more exposed to livestock than women by undertaking most agricultural activities such as pasturing and slaughtering [ 13 , 14 ]. Although incidences of human cases and livestock cases were significantly correlated, inconsistency was found in their spatial distributions in some provinces, e.g., Tibet and Sichuan, likely due to underreporting of anthrax case in livestock or the possibility that more than one person may contract the disease from a single animal [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an infectious disease caused by the bacterium (Bacillus anthracis), Anthrax is spread through the intestines (ingestion), lungs (inhalation), or skin (cutaneous) (Berger et al, 2014;Azarkar and Bidaki, 2016). Exposure to infected animals (or their skin, wool, and meat) is the usual pathway of anthrax to humans (Navdarashvili et al, 2015).…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Given this, food safety remains a concern. Spatial studies have previously reported clusters of cases of cutaneous anthrax located in towns along the animal migration corridors that spread from Kakheti near the border with Azerbaijan, through Kvemo-Kartli near Armenia and Turkey [ 14 ]. New research needs to estimate transmission potential of cutaneous anthrax cases along pastoralist routes, especially if those cases are pastoralists themselves.…”
Section: Discussionmentioning
confidence: 99%